Analisis hubungan lama jam kerja dengan burnout pada Perawat RSUD Palangka Raya selama pandemi covid-19 - Jeikawati; Mutiasari, Dian; Arifin, Syamsul; Suprihartini; Baboe, Dedy (Fakultas Kedokteran, Universitas Palangka Raya, 2023)
There is a considerable danger of mental exhaustion or burnout for nurses who are on the front lines of treating COVID-19, which could have a long-term negative impact on the standard of medical care. The research objective was to determine nurse burnout and prove the correlation between excessive working hours and nurse burnout during the COVID-19 pandemic. The method used is a quantitative descriptive study method with a cross-sectional design. The sample in this study was all nurses at Palangka Raya Regional Public Hospital, with a total sampling of 43 nurses. The research instrument was adopted from the Maslach Burnout Inventory (MBI). The correlation test used was Cramer's V, with the significance level of the variable test stated at p <0,05. The results of the study of 43 nurses showed no significant correlation between emotional burnout and working hours (p = 0.163), a significant correlation between depersonalization burnout and working hours (p = 0.019), and a significant correlation between burnout and a decrease in self-achievement (p = 0.033).